Salinomycin: anti-tumor activity in a pre-clinical colorectal cancer model - Klose, Johannes; Radhakrishnan, Praveen; Volz, Claudia; Schmidt, Thomas; Ulrich, Alexis; Dieter, Sebastian M.; Ball, Claudia R.; Glimm, Hanno; Schneider, Martin (PLOS ONE, 2019)
Objectives: Salinomycin is a polyether antibiotic with selective activity against human cancer stem cells. The impact of salinomycin on patient-derived primary human colorectal cancer cells has not been investigated so far. Thus, here we aimed to investigate the activity of salinomycin against tumor initiating cells isolated from patients with colorectal cancer. Methods: Primary tumor-initiating cells (TIC) isolated from human patients with colorectal liver metastases or from human primary colon carcinoma were exposed to salinomycin and compared to treatment with 5-FU and oxaliplatin. TICs were injected subcutaneously into NOD/SCID mice to induce a patient-derived mouse xenograft model of colorectal cancer. Animals were treated either with salinomycin, FOLFOX regimen, or salinomycin and FOLFOX. Human colorectal cancer cells were used to delineate an underlying molecular mechanism of salinomycin in this tumor entity. Results: Applying TICs isolated from human patients with colorectal liver metastases or from human primary colon carcinoma, we demonstrated that salinomycin exerts increased antiproliferative activity compared to 5-fluorouracil and oxaliplatin treatment. Consistently, salinomycin alone or in combination with FOLFOX exerts superior antitumor activity compared to FOLFOX therapy in a patient-derived mouse xenograft model of colorectal cancer. Salinomycin induces apoptosis of human colorectal cancer cells, accompanied by accumulation of dysfunctional mitochondria and reactive oxygen species. These effects are associated with expressional down-regulation of superoxide dismutase-1 (SOD1) in response to salinomycin treatment. Conclusion: Collectively, the results of this pre-clinical study indicate that salinomycin alone or in combination with 5-fluorouracil and oxaliplatin exerts increased antitumoral activity compared to common chemotherapy.
Gesehen am 29.07.2019